2014
DOI: 10.1093/jxb/eru354
|View full text |Cite
|
Sign up to set email alerts
|

A methylation status analysis of the apomixis-specific region in Paspalum spp. suggests an epigenetic control of parthenogenesis

Abstract: Apomixis, a clonal plant reproduction by seeds, is controlled in Paspalum spp. by a single locus which is blocked in terms of recombination. Partial sequence analysis of the apomixis locus revealed structural features of heterochromatin, namely the presence of repetitive elements, gene degeneration, and de-regulation. To test the epigenetic control of apomixis, a study on the distribution of cytosine methylation at the apomixis locus and the effect of artificial DNA demethylation on the mode of reproduction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 84 publications
4
52
0
Order By: Relevance
“…This has led to the hypothesis that the ACL region modulates epigenetic processes regulating parthenogenesis and endosperm formation. This is consistent with the finding that parthenogenesis is superimposed on sexual reproduction in this system and that DNA demethylation affects parthenogenesis but not apomeiosis [29,51]. In particular the homologue of subunit 3 of the ORIGIN RECOGNITION COMPLEX (ORC3), which is functional in sexual plants, is regulated by an apomixis specific antisense pseudogene [68] ( Table 1).…”
Section: Genes Located On Apomixis Loci Suggest That Different Regulasupporting
confidence: 89%
See 2 more Smart Citations
“…This has led to the hypothesis that the ACL region modulates epigenetic processes regulating parthenogenesis and endosperm formation. This is consistent with the finding that parthenogenesis is superimposed on sexual reproduction in this system and that DNA demethylation affects parthenogenesis but not apomeiosis [29,51]. In particular the homologue of subunit 3 of the ORIGIN RECOGNITION COMPLEX (ORC3), which is functional in sexual plants, is regulated by an apomixis specific antisense pseudogene [68] ( Table 1).…”
Section: Genes Located On Apomixis Loci Suggest That Different Regulasupporting
confidence: 89%
“…However, this view is challenged by new findings and hypotheses [6,18]. In some systems like Hieracium and likely also in Paspalum, apomixis is superimposed on sexual reproduction and dominantly silencing sexual reproduction [22,29]. Interestingly, thereby the sexual pathway can be re-established, suggesting that the gene regulatory program underlying sexual reproduction remains intact.…”
Section: The Developmental Flexibility Of Plant Reproduction Might Homentioning
confidence: 99%
See 1 more Smart Citation
“…Apomictic polyploids were likely derived from initially unstable diploid apomictic hybrids, and they seem to feature high heterozygosity necessary for sustenance of apomixis due to dosage-dependent gene regulation leading to efficient management of deleterious mutations (Archetti, 2004). In addition, ploidy shifts lead to changes in epigenetic landscape, for instance in DNA methylation within several loci, and concomitant transcriptional reprogramming wired by the RNA-dependent DNA methylation (RdDM) pathways required for initiation and maintenance of apomictic traits (Verhoeven et al, 2010; Hand and Koltunow, 2014; Podio et al, 2014; Zappacosta et al, 2014). Thus, hybridization-derived polyploidy could sustain apomixis in plant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary studies have brought to light many exciting discoveries regarding the epigenetic regulation of apomixis in angiosperms (Verhoeven & Preite, 2014;Zappacosta et al, 2014). Recent research has revealed that apomixis genes are highly methylated in some lineages (e.g., in Paspalum; Podio et al, 2014) and that epigenetic modifications are involved in the regulation of embryo and endosperm development in asexual flowering plants (Hojsgaard et al, 2014). Because DNA methylation can be influenced by abiotic stressors (Rapp & Wendel, 2005;Verhoeven et al, 2010) and has been shown to be heritable in some contexts (Feng et al, 2010;Ferreira de Carvahlo et al, 2016), it is reasonable to infer that epigenetic modification could lead to the heritable expression of apomixis in response to environmental cues.…”
Section: Investigating Genome Dynamics Of Apomixis In Fernsmentioning
confidence: 99%